Impact of natural and anthropogenic stresses on surface and groundwater supply sources of the Upper Awash Sub-Basin, Central Ethiopia - Birhanu, B.; Kebede, S.; Charles, K.; Taye, Meron Teferi; Atlaw, A.; Birhane, M. (Frontiers Media, 2021)
Improving water security is critical to delivering the best outcomes for development. In Ethiopia, the upper Awash sub-basin supports expanding urban and industrial areas, with increasing water demands. Studies have preferentially focused either on surface water hydrology or on groundwater characterization. However, novel tools are required to support the conjunctive use of surface and groundwater for competing users under potential climate change impacts. In this paper, we present research based on a WEAPMODFLOW link configured for four catchments in the upper Awash sub-basin (Akaki, Melka Kunture, Mojo, and Koka). The Akaki catchment supplies water for Addis Ababa city. Unlike most surface water hydrological models, both supply (surface water and groundwater) and demand (domestic, industrial, and livestock) are modeled. The tool was used to evaluate the impacts of population growth, leakage, expansion of surface and groundwater supply schemes, and climate change scenarios up to the year 2030. Considering the high population growth rate scenario for Addis Ababa city, the unmet domestic water demand may increase to 760 MCM in 2030. Water leakage through poor water supply distribution networks contributed about 23% of the unmet water demand. Though not significant compared with population and water loss stresses, climate change also affect the supply demand condition in the basin. Planning for more groundwater abstraction without considering additional surface water reservoir schemes will noticeably impact the groundwater resource, with groundwater levels projected to decline by more than 20 m. Even more groundwater level decline is observed In the Akaki catchment, where Addis Ababa city is located. Conjunctive use of surface and groundwater not only boosts the supply demand situation in the basin but will lift off some of the stresses from the groundwater resources. Even under the likely increase in temperature and low precipitation climate scenarios, the conjunctive use resulted in a significant increase in domestic water demand coverage from 26% for the reference condition to 90% in 2030, with minimum effect on the groundwater resources. To improve water security conditions through sustainable utilization of both surface and groundwater resources, policy responses need to consider surface and groundwater conjunctive use. Minimizing water leakage should also be given the highest priority.